The 5-HT1A Agonist Buspirone Decreases Liver Oxidative Stress and Exerts Protective Effect Against CCl4– Toxicity - Omar M.E.Abdel-Salam; Nermeen M. Shaffie; Nadia A. Mohammed; Eman R. Youness; Safaa M. Youssef Morsy; Amany A Sleem (Journal of Experimental and Clinical Toxicology, 2017)
We aimed to study the effect of buspirone, an anxiolytic drug and 5-HT1A agonist on liver injury induced by carbon tetrachloride (CCl4) in rats. Rats were orally treated with CCl4 (2.8 mL/kg in olive oil) along with buspirone at 10, 20 or 30 mg/kg once daily starting with CCl4 and for one week thereafter. Aspartate aminotransferase (AST) and alanine aminotransferase (ALT) as well as alkaline phosphatase (ALP) activities were determined in the serum. Markers of oxidative stress: lipid peroxidation (malondialdehyde; MDA), reduced glutathione (GSH), nitric oxide (nitrite/nitrate) levels were measured in the liver. Moreover, paraoxonase 1 activity was determined in the liver and serum. The administration of CCl4 led to significant increases in serum ALT, AST, and ALP activities. Results showed that there were significantly increased hepatic MDA, nitrite and decreased GSH levels. PON1 activity decreased both in the liver and serum, respectively. The immunohistochemical investigations using anti-caspase-3 antibody revealed that CCl4 caused apoptosis to many hepatocytes. DNA studies showed that CCl4 caused hypoploidy in hepatocytes. Rats treated with 20-30 mg/kg buspirone showed significant decrease in serum ALT and AST by 19.5-34.3% and 24.2-31.4%, respectively. Serum ALP decreased by 21.7% after 30 mg/kg buspirone. In the liver, the higher dose of the drug resulted in decreased MDA (by 15.8%), decreased nitric oxide (17.4%) and increased GSH (by 20.1%). Significantly increased serum PON1 activity by 43.9-53.5% was observed after treatment with 20-30 mg/kg buspirone. On histopathologic examination of liver sections, there was mild protective effect for the drug at 30 mg/kg. Sections stained with anti- caspase- 3 confirmed the results obtained from histopathological examination. Moreover, buspirone given at 30 mg/kg resulted in an increase in % of cells containing normal values of DNA. These results indicate that buspirone decreases liver oxidative stress and exerts protective effect against CCl4- toxicity. The study thus indicates more beneficial effects of buspirone as an anxiolytic drug and that the drug could be used safely in patients with liver disease.
Keywords: buspirone